3D Vertical Seismic Profiling Acquired Using Fibre-Optic Sensing Das – Results From The CO2CRC Otway Project. Issue 1 (1st December 2018) - Correa, Julia; Freifeld, Barry; Robertson, Michelle; Pevzner, Roman; Bona, Andrej; Popik, Dmitry; Tertyshnikov, Konstantin; Daley, Thomas
Abstract : Distributed Acoustic Sensing (DAS) is an optical interferometric method for acquisition of acoustic and seismic signals. It uses laser pulses that travel along the length of a fibre-optic cable and backscatter as they encounter small inconsistencies in the fibre. Impinging seismic waves cause strain on the cable, resulting in differences in phase of the backscattered light. Interest in DAS has increased significantly in the past decade as it is particularly suited for VSP acquisitions, including for permanent reservoir monitoring. Fibre-optic cables can be installed permanently in the well, cemented behind the casing or attached to tubing; they offer a relatively cheaper and efficient solution when compared to conventional borehole sensors. This study is part of the CO2CRC Otway Project. The Otway Project site is located approximately 240 km south-west of Melbourne, Australia. The Stage 2C of the project aims to monitor a small injection (15 kt) of CO2/CH4 gas mixture at a depth of approximately 1500 m. Here, we show the results of a 3D VSP survey acquired using DAS cable deployed on production tubing in the injector well. The DAS up-going wavefield shows a high level of noise. However, DAS is able to record the main reflections, including at the injection depth. After 3D migration of the data, noise levels reduce significantly. Events on DAS inline match with events on a corridor stack produced from a geophone check-shot data. Due to the directionality pattern, DAS was only able to image up to approximately 300 m radius from the well.